(untitled) (Federal University Gusau Faculty of Education Journal, 2026)
Vignettes are increasingly used in science education as instructional and assessment tools for examining learners’ conceptual understanding, reflective thinking, and decision-making abilities. In the context of Basic Science education, a vignette is a short, context-based scenario drawn from learners’ everyday experiences and aligned with curriculum concepts such as health, environment, energy, matter, and safety. This paper discusses the concepts of vignettes, their major types-descriptive, problem-based, reflective and decision-oriented-and their application in Basic Science teaching and research. Both offline (paper-based) and online (digital) vignettes are highlighted as flexible approaches suitable for varying classroom contexts. Criteria for constructing good vignettes include clarity of purpose, realism, cultural relevance, alignment with Basic Science learning objectives, appropriate cognitive demand, and the ability to elicit reasoning rather than rote responses. Research evidence indicates that vignettes enhance learner engagement, promote higher-order thinking, uncover misconceptions, and support the application of scientific concepts to real-life situations. However, limitations such as response bias, over-simplification of complex scientific issues, and challenges in scoring and interpretation are also noted. The paper concludes that vignettes are effective learner-centred tools that complement traditional teaching and assessment methods in Basic Science Education. It is therefore suggested that Basic Science teachers and curriculum developers integrate vignette-based strategies into classroom instruction and assessment, while providing adequate training on vignette design and use to maximise their educational value.